On Contra-$(τ_1,τ_2)p$-continuous Functions (European Journal of Pure and Applied Mathematics, 2025)
This paper presents a new class of functions called contra-$(τ_1,τ_2)p$-continuous functions.Furthermore, several characterizations and some properties concerning contra-$(τ_1,τ_2)p$-continuousfunctions are considered.
Keywords: $τ_1τ_2$-open set; contra-$(τ_1,τ_2)p$-continuous function